Design and Simulation of an 8-Lead Electrical Capacitance Tomographic System for Flow Imaging - Ghaly, S. M. A.; Al-Snaie, K. A.; Khan, M. O.; Shalaby, M. Y.; Oraiqat, M. T. (Engineering, Technology & Applied Science Research, 2021)
Electrical Capacitance Tomography (ECT) is a method for determining the dielectric permittivity distribution inside an object from measurements of external capacitance. The technique differs from conventional tomographic methods in which high-resolution images are formed from slices of the material. The measuring electrodes, which are metal plates, must be large enough to give a measurable change in capacitance. The main objective of this paper is the implementation and simulation of 8 external electrode ECT systems in order to increase the quality of reconstructed permittivity images while preserving the simplicity of design and fulfilling the demand for real-time process tomography. A complete sensor model was developed to improve the accuracy of the forward validation, especially the validation of measured data from neighboring electrodes. A prototype ECT sensor with high sensitivity was designed that can be applied to all materials which have low electrical conductivity. The capacitance between different electrode pairs is calculated for some typical permittivity distributions based on LabVIEW and MATLAB. The obtained capacitance data can be used to reconstruct images. The sensitivity distributions for the ECT sensors with different numbers of electrodes were analyzed. Preliminary tests were performed and the developed prototype showed good performance. The developed concept contributes to the study and comprehension of the ECT systems that can be used for the monitoring of oil-gas flow.